Stepwise transvenous lead extraction due to pacemaker pocket infection following lactational mastitis complicated with breast abscess - Lidija Poposka; Dejan Risteski; Dimitar Cvetkovski; Bekim Pocesta; Filip Janusevski; Zhan Zimbakov; Ivan Trajkov; Dime Stefanovski; Mateja Logar; Jus Ksela (BMC, 2024)
Abstract Background Lactational mastitis is a common painful and debilitating inflammation of breast tissue, generally treated conservatively or with pus puncture in case of breast abscess. However, treating mastitis in patients with implantable surgical material located in the affected breast region can be extremely challenging. We present an unusual case of lactational mastitis complicated by pacemaker pocket infection in a breastfeeding mother. Case presentation A 35-year-old pacemaker-dependent female developed lactational mastitis seven weeks postpartum. Initially, the condition was treated conservatively with analgesics and antibiotics. After abscess formation, pus was aspirated using fine-needle aspiration technique. Four weeks after mastitis resolution, pacemaker pocket infection developed. According to current cardiovascular implantable electronic device infection treatment guidelines a complete surgical extraction of the entire electronic system, followed by targeted antibiotic treatment and reimplantation of a new device after infection resolution, was recommended. However, after thorough discussion with the young woman and her family and after detailed review of surgery-related risks, she declined a potentially high-risk surgical procedure. Thus, only the pulse generator was explanted; pacing leads positioned in the sub-pectoral pocket; new pacemaker implanted on the contralateral side and broad-spectrum antibiotic therapy continued for six weeks. After breastfeeding cessation, and with chronic fistula development at the primary pacemaker implantation site, the possibility of delayed surgical intervention including complete extraction of retained pacemaker leads was again thoroughly discussed with her. After thoughtful consideration the woman consented to the proposed treatment strategy. A surgical procedure including transvenous lead extraction through the primary implantation venous entry site, using hand-powered bidirectional rotational sheaths, was successfully performed, removing all retained leads through the left subclavian venous entry site, and leaving the fully functional and clinically uninfected pacemaker on the contralateral site intact. Conclusion Although patients' decisions for delayed extraction in a case of cardiovascular implantable electronic device infection should be discouraged by attending physicians and members of interdisciplinary teams, our case shows that a stepwise treatment strategy may be successful as a bailout clinical scenario in patients with specific requests, demands and / or clinical needs.